Um estudo histórico do curso de matemática da Universidade Estadual de Maringá: a criação e os primeiros anos - Araujo Neto, Antonio Peixoto de (2016)
This research had intended to investigate the undergraduate course of Mathematics at the State University of Maringá (UEM), since its creation in 1969 and its early years until 1982. This research is part of the History of Mathematics in Brazil and the historical analyses were made according to the prospects of bibliographical research, documental and oral researches. In order to answer the question "How was the creation and the development of the Mathematics course at UEM"? the following pathway was taken: looking for documents that could refer to the creation of the course at archival centers at the university, doing an interview with a pioneer of the course, the Professor Amaury Meller, analyzing the political and economic contexts in a local and state perspectives, and conducting a parallel historical analysis among the Mathematics courses in the state of São Paulo. People that took part on the time of the creation and the early years are presented based on the documents founded: the first professors and graduate students. In addition the undergraduate program and its changes during the period studied in this research are presented and an interview was done with the professor João Cesar Guirado, the supporter for the creation of the subject of Mathematics Teaching Instrumentation inserted in 1982. All of the analyses have concluded that the Mathematics Course at UEM was created to serve as a base to the Engineering courses and fill the teachers' gap of secondary education that the region was suffering at that time.